Here's the question you clicked on:
kymber
How to do composition of functions?
could you give a question as an example
okay so you have f(x)=2x-1 g(x)=x+2 so you want gf this means you will do g(f) so your g function is g(x)=x+2 now g(f)=f+2 because it replaces all the x's but you know that f(x)=2x-1 so you are doing g(f) which is equal to g(2x-1) so your g function is g(x)=x+2 instead of x you will replace all x's with 2x-1 so g(2x-1)=2x-1+2 g(2x-1)=2x+1
So composition is just multiplying??
no you had gf that is a function of f but you know that f is 2x-1 so you sub that into your function for g you are replacing the function on the right with its function of x then the substituting it into the function that follows the one on the right like here the function the right is f which is 2x-1 you subbed that into the function for g
So composition is putting f into g?
Oh.. okay. Thanks \(\huge\ddot\smile\)
if it makes it easier to understand try this you have gf you could re write it to be gf(x) you know f(x)=2x-1 so you can rewrite it to be g(2x-1) sub it into the g function